Reviving knowledge: A 70-year gap in the host-parasite relationship between Trichodectes galictidis Werneck, 1934 (Ischnocera: Trichodectidae) and Galictis cuja (Molina, 1782) (Carnivora: Mustelidae) - Bassini-Silva, Ricardo; Quadros, Rosiléia Marinho de; Castilho, Pedro Volkmer de; Mendes, Luisa Padaratz; Souza, Gabriela Cristini de; Alves, Carolina Feltes; Barros-Battesti, Darci Moraes [UNESP]; Jacinavicius, Fernando de Castro (Elsevier, 2025)
Galictis cuja is one of the least known mustelids in South America, with its frequency and distribution poorly documented across the Neotropical region from Mexico to Brazil. In February 2024, a female was rescued by fishermen on Porto Beach in Imbituba, Santa Catarina. A clinical examination revealed ectoparasites on the animal, identified as Trichodectes galictidis, a louse species not detected in these animals for over 70 years. This study explores the revival of knowledge regarding the host-parasite relationship between Trichodectes galictidis and Galictis cuja, highlighting a significant research gap. Through a literature review and new data obtained using scanning electron microscopy (SEM), the study documents previously unrecorded characteristics of the parasite. The findings not only revive knowledge of this relationship but also underscore the importance of continued research into the ecological and parasitic dynamics of this species, which remain largely unexplored in the Neotropical region.
Keywords: Chewing louse; Ectoparasites; First record; Mustelids